Anisotropic velocity models for (3-D) seismic imaging of the Lower Seve Nappe in Jämtland, Sweden. Issue 1 (20th August 2021) - Kästner, Felix; Klaeschen, Dirk; Berndt, Christian; Pierdominici, Simona; Hedin, Peter
SUMMARY: Strong anisotropy of seismic velocity in the Earth's crust poses serious challenges for seismic imaging. Where in situ seismic properties are not available, the anisotropy can be determined from velocity analysis of surface and borehole seismic profiles. This is well established for dense, long-offset reflection seismic data. However, it is unknown how applicable this approach is for sparse seismic reflection data with low fold and short offsets in anisotropic metamorphic rocks. Here, we show that anisotropy parameters can be determined from a sparse 3-D data set at the COSC-1 borehole site in the Swedish Caledonides and that the results agree well with the seismic anisotropy parameters determined from seismic laboratory measurements on core samples. Applying these anisotropy parameters during 3-D seismic imaging improves the seismic image of the high-amplitude reflections especially in the vicinity of the lower part of the borehole. Strong reflections in the resulting seismic data show good correlation with the borehole-derived lithology. Our results aid the interpretation and extrapolation of the seismic stratigraphy of the Lower Seve Nappe in Jämtland and other parts in the Caledonides.